2017
DOI: 10.1002/ijc.30819
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab or nimotuzumab plus intensity-modulated radiotherapy versus cisplatin plus intensity-modulated radiotherapy for stage II-IVb nasopharyngeal carcinoma

Abstract: To compare intensity-modulated radiotherapy (IMRT) with cisplatin (CDDP) versus cetuximab (CTX) and nimotuzumab (NTZ) for Stage II-IVb Nasopharyngeal Carcinoma (NPC). A total of 1,837 patients with stage II-IV NPC who received IMRT plus CTX or NTZ, or CDDP between January 2009 and December 2013 were included in the current analysis. Using propensity scores to adjust for potential prognostic factors, a well-balanced cohort of 715 patients was created by matching each patient who underwent IMRT plus concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 27 publications
4
41
1
Order By: Relevance
“…Overall, grade 3‐4 toxic events were more common in the IC + CTX/NTZ group than in the IC alone group, and significant differences mainly occurred in anti‐EGFR therapy‐related toxicities like skin reactions and mucositis. However, the incidence of severe skin and mucositis in our study was significantly less compared with the results in previous studies . Undoubtedly, CTX/NTZ aggravated radiation‐induced skin and oral mucositis.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Overall, grade 3‐4 toxic events were more common in the IC + CTX/NTZ group than in the IC alone group, and significant differences mainly occurred in anti‐EGFR therapy‐related toxicities like skin reactions and mucositis. However, the incidence of severe skin and mucositis in our study was significantly less compared with the results in previous studies . Undoubtedly, CTX/NTZ aggravated radiation‐induced skin and oral mucositis.…”
Section: Discussioncontrasting
confidence: 81%
“…However, the incidence of severe skin and mucositis in our study was significantly less compared with the results in previous studies. 10,[12][13][14] Undoubtedly, CTX/NTZ aggravated radiation-induced skin and oral mucositis. Another reason may be that the total dose used in the induction phase is less than that used in concurrent phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the former, Huang et al demonstrated that concurrent administration of nimotuzumab and celecoxib cooperatively enhanced the cytotoxicity and radiosensitivity of NPC cells (CNE-2) in vitro [10]. Clinical studies have shown that cetuximab or nimotuzumab, combined with radiotherapy can enhance the efficacy of radiotherapy with a better safety profile [11][12][13].…”
Section: Introductionmentioning
confidence: 99%